Explainable XGBoost Models for Predicting Generalized Anxiety Disorder from Digital Mental Health Indicators - Knaul , Airton; Giongo , Citieli (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: This study aimed to develop and evaluate an explainable XGBoost model for predicting generalized anxiety disorder from psychological, behavioral, and digital mental health indicators among Canadian adults. Methods and Materials: This cross-sectional predictive study was conducted with 2,412 adults from Canada. Data were collected using standardized measures of generalized anxiety, psychological distress, depressive symptoms, sleep quality, smartphone addiction, and social media addiction, along with a structured digital lifestyle questionnaire assessing daily screen time, sleep duration, physical activity, technology-related stress, digital notification frequency, remote work hours, online gaming, and demographic characteristics. Generalized anxiety disorder risk was classified using the GAD-7 clinical cut-off. After preprocessing, missing-data imputation, feature encoding, and feature engineering, the dataset was divided into stratified training and testing subsets. An XGBoost classification model was optimized through cross-validation, and model explainability was examined using SHapley Additive exPlanations. Findings: Generalized anxiety symptoms were strongly correlated with psychological distress (r = .79, p < .01) and depressive symptoms (r = .74, p < .01), and moderately to strongly correlated with poor sleep quality (r = .61, p < .01), smartphone addiction (r = .54, p < .01), and social media addiction (r = .46, p < .01). The optimized XGBoost model showed excellent predictive performance on the independent test set, with accuracy of 91.8%, precision of 89.6%, recall of 88.2%, specificity of 93.5%, F1-score of 88.9%, ROC-AUC of .957, PR-AUC of .944, balanced accuracy of 90.9%, Matthews correlation coefficient of .819, and Brier score of .081. SHAP analysis identified psychological distress, depression, sleep quality, smartphone addiction, previous mental health diagnosis, screen time, social media addiction, and technology-related stress as the most influential predictors. Conclusion: Explainable XGBoost modeling demonstrated high accuracy and interpretability for predicting generalized anxiety disorder from digital mental health indicators, supporting its potential use in early screening, risk stratification, and personalized digital mental health assessment.